Content and Language Integrated Learning in Tertiary Education: Perspectives on Terms of Use and Integration - Zarichna, Olena; Buchatska, Svitlana; Melnyk, Liudmyla; Savchuk, Tetiana (Lesya Ukrainka Eastern European National University, 2020)
This paper reports on a classroom investigation into a tertiary variation of content and language integrated learning (CLIL) as well as addresses the conceptual and methodological parameters of this method as distinguished from the other two content-based English-taught courses: ESP and EMI. A special challenge for this research was to study the functionality of CLIL in the university settings in terms of content retention and language acquisition as well as the development of communicative culture in university students. With this purpose we conducted a pilot project on CLIL also designing a triple vector observation scheme (content retention; language acquisition; communication culture) and adding the high order thinking skills dimension as a pivotal learning goal in a CLIL-based English classroom. The project comprised 8 syllabi-based sub-modules that featured scientific content and was conducted among 78 humanities majors. Findings show that students’ cognitive and communicative needs do not find sufficient support in the existing L2 courses to which CLIL may serve as a solution. Introduction of CLIL even at the level of a variable sub-module may considerably raise students’ satisfaction with L2 courses and provide a reliable backing in the development of their academic thinking and communicative culture.
Keywords: Content and Language Integrated Learning (CLIL); English for Specific Purposes (ESP); English as a Medium of Instruction (EMI); content-based instruction; Basic Interpersonal Communication System (BICS); Cognitive Academic Language Proficiency (CALP); high order thinking skills